Structural and dynamic analysis of demographic processes in the Republic of Mari El - E. V. Kostromina (Статистика и экономика, 2017)
Modern regional economic development is inseparably linked with the development of the human potential of the region under study, the main contribution to the formation of which is made by the demographic processes of the region. The study of these processes, their dynamics, development trends, factors of their formation is necessary for presenting a contemporary picture of the mutual influence of social, demographic and economic processes. The relevance of this study is related to the increasing role of demographic processes in the social and economic development of the region. The review of domestic and foreign studies related to the study of economic and demographic processes made it possible to identify the need for a more detailed analysis of forming the population age structure, the various development types of which may have different effects on the processes of shaping the labor resources of the region. The purpose of the study is a statistical analysis of the dynamics of indicators of the demographic development of the Republic of Mari El and the identifi cation of major socio-economic trends that affect the formation of the age and sex structure of the population. To achieve this goal, a number of tasks were accomplished: the indicators of the demographic development of the Republic of Mari El for 2000-2017 were collected and processed; the qualitative changes in the demographic structure of the Republic were defi ned; the factors of change in the sex and age structure of the population were determined; the role of demographic trends in various stages of forming labor resources of the Republic of Mari El was outlined; the conclusions were drawn about the nature of the dynamics of natural growth and the role of the age structure in the change in the birth rate and mortality of the region under study; the forecast of the dynamics of the number of population age cohorts in the Republic of Mari El up to 2056 was made; the conclusions were drawn on the type of reproduction of the Republic of Mari El population. The collection of indicators reflecting the structure and dynamics of the population, migration trends, birth rate, mortality, health and other demographic characteristics in terms of the age structure of the population and the type of residence made it possible to draw conclusions about the main factors of the demographic development of the Republic of Mari El. First, it is the population structure that forms the Republic’s reproductive and labor potential, as well as the migration behavior of the Republic of Mari El population. Secondly, the incidence rate, affecting both the mortality rate in the region, and the birth rate. Thirdly, the way of life, which is the catalyst for many socio-demographic processes taking place in the Republic. Fourthly, the standard of living, which includes both the material living conditions and the infrastructure of the Republic. This factor, combined with the way of life, forms the conditions for reducing mortality and increasing the birth rate in the Republic; it determines migration trends: a region with a high standard of living is easier to attract immigrants, fewer inhabitants of a competitive region will want to leave it. Detailing the process of forming the demographic potential allowed to make a forecast of the future size and sex-age structure of the population of the Republic of Mari El. Using the age-shifting method, the following indicators were obtained: total population, working-age population, demographicburden factors, etc. Each indicator was presented in three variants of the forecast: high, low and medium, which allowed drawing conclusions about the future trends of socio-economic development under the infl uence ofvarious factors.